Search for resonant diboson production in the ℓℓq¯q final state in pp collisions at √s = 8 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2015)
This paper reports on a search for narrow resonances in diboson production in the q¯q final state using pp collision data corresponding to an integrated luminosity of 20 fb−1 collected at √s = 8 TeV with the ATLAS detector at the Large Hadron Collider. No significant excess of data events over the Standard Model expectation is observed. Upper limits at the 95 % confidence level are set on the production cross section times branching ratio for Kaluza–Klein gravitons predicted by the Randall–Sundrum model and for Extended Gauge Model W bosons. These results lead to the exclusion of mass values below 740 and 1590 GeV for the graviton and W boson respectively.